Digital transformation in marketing 2025: the role of artificial intelligence in improving customer experience - Syawaluddin Syawaluddin; Desi Amanda; Riski Irawan; Boster Sitio; Sumitro Sumitro (Jurnal Sains, Teknologi & Komputer, 2026)
The development of digital technology in 2025 shows increasingly significant acceleration, particularly marked by the increasing use of Artificial Intelligence (AI) in modern marketing strategies. AI integration enables companies to create a more personalized, responsive, and adaptive customer experience (CX) through the application of predictive analytics, marketing automation, and real-time data processing. This article aims to analyze the strategic role of AI in improving customer experience in the context of digital marketing in 2025. The research method used is a systematic literature review of 35 scientific articles, industry reports, and reputable international publications relevant to the study topic. The results of the analysis show that AI contributes significantly to improving customer experience through four main dimensions: data-driven personalization, intelligent customer interactions, service and operational efficiency, and accurate and contextual product recommendation systems. These findings confirm that AI integration is no longer optional, but rather a strategic necessity for companies in strengthening digital transformation, increasing customer loyalty, and maintaining business competitiveness in the increasingly dynamic digital marketing era.